ANALYSIS OF PHYSICAL ACTIVITY AND NITRIC OXIDE ON THE INCIDENCE OF HYPERTENSION AMONG THE ELDERLY IN THE WORKING AREA OF NANGGALO PUBLIC HEALTH CENTER IN 2025 : HYPERTENSION AMONG THE ELDERLY - Mukhlis, Mukhllis; Syahrial, Syahrial; Elda, Frima; Symond, Denas; Elnovriza, Deni; Yuniritha, Eva (STIKes Mandala Waluya Kendari, 2025)
Background: Hypertension is a condition characterized by blood pressure rising above normal levels, commonly referred to as high blood pressure. Hypertension is defined as a systolic blood pressure of ≥140 mmHg and diastolic pressure of >90 mmHg. It is a disease with a high prevalence of disability and mortality rates each year and is often referred to as “the silent killer.” This study aimed to determine the relationship between physical activity and nitric oxide levels with the incidence of hypertension among the elderly at Nanggalo Public Health Center. Methods: This study employed a quantitative approach with a cross-sectional design. A total of 137 respondents were selected using a simple random sampling technique. The research was conducted from March to April 2025. Data analysis was performed using Chi-square and Pearson Correlation tests. Results: The Chi-square test showed a significant relationship between physical activity and the incidence of hypertension (p = 0.006) at Nanggalo Public Health Center, indicating that physical activity is associated with hypertension among the elderly. Meanwhile, the Pearson Correlation analysis revealed no significant relationship between nitric oxide intake and hypertension (p = 0.146; p > 0.05). Conclusion: There is a significant relationship between physical activity and the incidence of hypertension among the elderly. However, there is no significant relationship between nitric oxide intake and the incidence of hypertension.